2003
DOI: 10.1046/j.1365-2249.2003.02160.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating concentrations of soluble granzyme A and B increase during natural and experimental Plasmodium falciparum infections

Abstract: SUMMARYRelease of soluble Granzymes (sGranzymes) is considered to reflect activation of cytotoxic T lymphocytes and NK cells. sGranzymes and a number of pro-inflammatory cytokines were measured in plasma of malaria patients with natural or experimentally induced Plasmodium falciparum infections. Concentrations of sGranzyme A and B, IL-10, IL-12p70 and CRP were significantly increased in African children presenting with clinical malaria; IL-10 and CRP concentrations were significantly correlated with disease se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 30 publications
6
68
0
2
Order By: Relevance
“…In Malawian children with severe malaria, mortality was observed to increase with increasing serum TNF-α [31] , and in plasma of African children, TNF-α levels were found to be higher among those with cerebral malaria (CM) than in those with uncomplicated P. falciparum malaria [23] . A recent experiment involving P. falciparum infection in malaria-naive individuals has shown a coordinated increase in the level of pro-inflammatory cytokines, including IFN-γ, IL-12, and IL-8, in serum at the time when parasite emergence from the liver and the first appearance of parasitized erythrocytes [32] . In vitro studies have demonstrated that PRBCs can induce the production of TNF-α, IL-12, and IFN-γ by PBMCs of naive donors within 10 h [33] .…”
Section: Increased Activation Of Nf-κb In Blood Mononuclear Cells Of mentioning
confidence: 99%
“…In Malawian children with severe malaria, mortality was observed to increase with increasing serum TNF-α [31] , and in plasma of African children, TNF-α levels were found to be higher among those with cerebral malaria (CM) than in those with uncomplicated P. falciparum malaria [23] . A recent experiment involving P. falciparum infection in malaria-naive individuals has shown a coordinated increase in the level of pro-inflammatory cytokines, including IFN-γ, IL-12, and IL-8, in serum at the time when parasite emergence from the liver and the first appearance of parasitized erythrocytes [32] . In vitro studies have demonstrated that PRBCs can induce the production of TNF-α, IL-12, and IFN-γ by PBMCs of naive donors within 10 h [33] .…”
Section: Increased Activation Of Nf-κb In Blood Mononuclear Cells Of mentioning
confidence: 99%
“…La production d'IL18 serait également un élément important de la réponse immunitaire contre le parasite [12][13][14]. De plus, au cours du paludisme de l'enfant, les concentrations de granzymes A et B solubles, ainsi que des cytokines (IL-12p70, IL-10), sont augmentées dans le sérum [15]. Par ailleurs, la réponse immunitaire précoce a été étudiée chez des volontaires sains non immuns infectés par une souche de Pf étendue à plusieurs autres souches de Pf, y compris certains isolats cliniques [20].…”
Section: Une Réponse Précoce Des Cellules Natural Killerunclassified
“…Plasma granzymes are also elevated during viral infections (human immunodeficiency virus-1, Epstein-Barr virus) and certain bacterial infections (16,18,19). These extracellular granzymes may arise via constitutive (nonspecific) secretion after CLs degranulate (20) or may escape the immunological synapse as the CL degranulates, disengages, and moves onto another target (21,22).…”
mentioning
confidence: 99%